Analisis Marketing Mix 7P terhadap Minat Kunjungan Ulang Pasien di Klinik Khasanah Medika dan Baitul Syifa Tahun 2024 - Aditya Reza Prianugraha; Agus Hadian Rahim; Bambang Sukajie (Jurnal Syntax Admiration, 2024)
Number of repeat visits from old patients in 2023 at the Baitul Syifa Clinic is 74%, while at the Khasanah Medika Clinic ber of patient visits has an impact on low clinic income, so that Marketing Mix 7P can be used as an appropriate marketing strategy to increase patient interest in repeat visits. The purpose of this research analyze influence Marketing Mix 7P on interest in re-visiting patients at the Baitul Syifa Clinic and Khasanah Medika Clinic and analyzing the variabels that have the most dominant influence on interest in re-visiting patients. This type of research is quantitative research by design cross sectional. Sampling technique with Purposive sampling. The subjects of this research were outpatients at the Baitul Syifa Clinic and Khasanah Medika Clinic. The number of samples in this study was 100 patients from each clinic. The research instrument uses a questionnaire with statistical tests chi square. The research results stated that Marketing Mix 7P has a significant effect on interest in repeat visits by Baitul Syifa clinic patients, including variabels Product with a value of 81% (p=0,000), Price with a value of  79% (p=0,000), Promotion with a value of  78% (p=0,000), Place with a value of 80% (p=0,000), People (p=0,000), Process with a value of 80% (p=0,000), and Physical Evidence with a value of  78% (p=0.000), whereas Marketing Mix at the Khasanah Medika clinic which consists of Product with a value of 80% (p=0,000), Price with a value of 80% (p=0,000), and Place with a value of 78% (p=0.000) has a significant effect on patient interest in repeat visits, other variabels, namely Promotion with a value of 43% (p=0,909), People with a value of 67% (p=0,970), Process with a value of 68% (p=0,268), and Physical Evidence with a value of 48% (p=0.983).